Assessment of the impact of a fully electrified postal fleet for urban freight transportation. (July 2021) - Martínez, Miguel; Moreno, Asier; Angulo, Ignacio; Mateo, Carlos; Masegosa, Antonio David; Perallos, Asier; Frías, Pablo
Highlights: Network reinforcements can be avoided with a decentralized operation hub. A centralized operation hub would require longer routes and more consumption. The reduction of emissions with a centralized operation hub would be higher. Valley charging mitigates network reinforcements and reduces cost of energy supply. Combining a route optimization model with a reference network model has strong potential. Abstract: The progressive electrification of urban distribution fleets, motivated by the consolidation of electric vehicle technology and by the mobility advantages that cities grant to non-polluting vehicles, poses future challenges that affect electrical distribution networks. This paper simulates the main last mile distribution models that can be adopted in a mega-city such as Madrid. In particular, the impact of carrying out the full load of the last mile distribution by means of electric vehicles is analyzed. Two fundamental aspects are studied, the efficiency of the different routes developed by each transport vehicle and the impact that these routes have in the electrical distribution network. For this purpose, an intelligent route planner, capable of optimizing the distribution of the load among the number of vehicles available in each postal service hub (PSH), is combined with a Reference Network Model that designs and expands the distribution network to supply consumers and electric vehicles. Several scenarios in terms of location and segmentation of postal service hubs are analyzed. From this analysis, it is concluded that reinforcements on the distribution network are avoided if the operation is decentralized (using fourteen PSHs), since a centralized operation (a single PSH) would require longer routes with higher energy consumption. Moreover, decentralized operation would enhance the emissions reduction achieved by electrifying the fleet, since the estimated absolute emissions of the electrified fleet for a decentralized scenario are up to 50% lower compared to a centralized one. Finally, the results reveal that smart charging strategies also contribute to lessen the incremental costs in the distribution network, in addition to significantly reducing the cost of energy supply.